Social networks and biographical method - M. A. Panarina; O. A. Kulikova (Цифровая социология)
The concept of storytelling as one of the modern varieties of the biographical method has been considered. An example of analyzing the history of social networks has been suggested, which allows us to reveal the full potential of this method for the development of digital sociology. Social networks expand horizontal communication and create opportunities for rapid, networked dissemination of information. Almost barrier-free entry and wide circulation make it possible to use a longknown and  proven tool more widely. Storytelling allows you to get visual, emotional, and evaluative components of any biography. Information obtained using this method gives us an opportunity to study several layers of a particular biography and build a network of social relationships of the individual, that is, to look at these or other facts of the biography from different points of view of the participants of the events. The story analyzed in this paper is interesting for its genre: a personal narrative created at the initiative of the online magazine Lady.mail.ru. The communication channel that is used to broadcast the story affects on the content of the message being transmitted, thus being an element of the story itself. For example, the same story can be told differently through text and video, respectively, having a different impact, or vice versa, different tools may be used to transmit the same story, depending on the specifics of the transmission channel. Each story has an individual storyteller, it is an element of a larger, multi-voiced story. Modern digital technologies have simplified and expanded the possibilities of the biographical method, since a huge amount of biographical information is voluntarily uploaded to social networks by millions of their users from different segments of the population, which allows us using this method to analyze most of the problems that are in the interests of modern sociological thought.